2019
DOI: 10.36740/wlek201903112
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Cardiac Arrhythmias In Pregnant Women

Abstract: Introduction: Cardiac arrhythmia often occurs in the gestational period of pregnant women, contributing to the development of complications of pregnancy, childbirth and perinatal pathology, which requires a more thorough examination of pregnant women and antiarrhythmic treatment, which in turn increases the risk of complications pregnancy and childbirth. Many types of arrhythmias occur in women without structural damage to the cardiovascular system. The aim is to study the occurrence of cardiac rhythm disturba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Approximately, there is an increase of 10 beats per min in the resting pulse rate during pregnancy. Marked changes in the maternal heart rate occur in the second trimester of pregnancy and the increase in gravidity imposes an increased risk of cardiac disturbances [3,4]. The blood volume increases by an average of 50% markedly from the latter half of the first trimester.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately, there is an increase of 10 beats per min in the resting pulse rate during pregnancy. Marked changes in the maternal heart rate occur in the second trimester of pregnancy and the increase in gravidity imposes an increased risk of cardiac disturbances [3,4]. The blood volume increases by an average of 50% markedly from the latter half of the first trimester.…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by a higher incidence of new-onset arrhythmias in the second trimester during pregnancy. Afanasiuk et al [ 66 ] also observed a higher incidence of new-onset arrhythmias in the second trimester. They explained this trend as a result of compression of the cardiovascular structures by the enlarged uterus in the second trimester.…”
Section: Discussionmentioning
confidence: 99%